Antioxidant Activity of Stem Bark Ethanolic Extracts of Calophyllum pulcherrimum, C. soulattri, and C. teysmannii - Eris Septiana; Partomuan Simanjuntak (Buletin Penelitian Tanaman Rempah dan Obat, 2018)
The decreased air quality due to severe pollution causes the formation of free radicals in the body. Antioxidants counteract free radicals compounds and are beneficial to health. Calophyllum plants is one of the natural antioxidants source. The study was aimed to determine the best antioxidant activity of ethanolic extracts of stem bark both single and combinations of three species of Calophyllum. The study was conducted from September to December 2017 at the Natural Product Chemistry Laboratory, Research Center for Biotechnology LIPI, Cibinong, West Java. The experiment consisted of seven treatments, repeated three times.  The treatments consisted of ethanolic stem bark extracts of a) C. pulcherrimum b) C. soulattri (CS), c) C. teysmannii (CT), d) combination of C. pulcherrimum and C. soulattri (CP+CS), e) combination of C. pulcherrimum and C. teysmannii (CP+CT), f) combination of C. soulattri and C. teysmannii (CS+CT), and g) combination of C. pulcherrimum, C. soulattri and C. teysmannii (CP+CS+CT) with the ratio of mixed extract was 1 : 1 for treatments with two combinations and 1 : 1 : 1 for three combinations. The antioxidant activity was evaluated using DPPH free radical scavenging  methods.  The  total  phenolic   and   flavonoids   content   assays   were conducted base on the reaction of follin-ciocalteu and aluminum chloride reagents respectively.  The results showed that combination of Calophyllum stem bark ethanolic extracts revealed higher antioxidant activity, total phenol and flavonoid content compared to its sole extract. CP+CS+CT treatment has the lowest IC50 value at 3.12 mg.l-1 so that it has the potential as a source of natural antioxidants.